Efektivitas Suplementasi Zink Terhadap Lama Rawat Inap pada Pasien Pneumonia Anak: A Systematic Review of Randomized Controlled Trials - Dewi, Ni Luh Putu Yunia; Mayangsari, Ayu Setyorini Mestika; Adnyana, I Gusti Agung Ngurah Sugitha (Universitas Udayana, 2023)
Zinc supplementation was reported increasing pneumonia in child outcomes, which one is the length of hospital stay, but still controversial. This review will discuss about effectivity of zinc supplementation for the length of hospital stay in children hospitalized with pneumonia in forms systematic review. Searching was performed at CENTRAL, PubMed, and ProQuest for journal published from 2015 to 2020 which evaluate the effectivity of zinc supplementation for the length of hospital stay in children hospitalized with pneumonia. This review based on writing guidelines by Cochrane Textbook of Systematic Review. There are four studies relevant to this review. All studies are blinded study. A total of 1.359 children hospitalized with pneumonia, percentage of a male around 59%. A total of 680 participants received zinc supplementation as addition for standard antibiotics. Participants were 1 to 60 months of age. All studies measure baseline serum zinc levels. Two studies reported significant results, while two other study conversely. Effectivity of zinc supplementation has not been concluded yet. Based on critical appraisal, the author attends to agree with two studies that conduct in Asia, in which the populations were similar to Indonesia. In that study found zinc supplementation effective to decreases the length of hospital stay in children hospitalized with pneumonia. There is no fatal adverse effect of zinc supplementation was reported.